2001
DOI: 10.1093/hmg/10.26.3009
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygosity for the neurofibromatosis 1 (NF1) tumor suppressor results in abnormalities in cell attachment, spreading and motility in astrocytes

Abstract: Individuals with the neurofibromatosis 1 (NF1) tumor predisposition syndrome develop low-grade pilocytic astrocytomas at an increased frequency. Previously, we demonstrated that astrocytes from mice heterozygous for a targeted mutation in the Nf1 gene (Nf1+/- astrocytes) exhibit a cell autonomous growth advantage associated with increased RAS pathway activation. In this report, we extend our initial characterization of the effect of reduced Nf1 gene expression on astrocyte function by demonstrating that Nf1+/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 45 publications
4
27
0
Order By: Relevance
“…However, there is accumulating evidence that haploinsufficiency or reduced expression of tumor suppressor genes can influence carcinogenesis (Berger et al 2011). Indeed heterozygosity for Nf1 causes cancer-like cellular phenotypes in astrocytes (Gutmann et al 1999;Bajenaru et al 2001;Gutmann et al 2001). We note that a recent cancer genome study did not report a high frequency of NF1 CNAs (Curtis et al 2012).…”
Section: Discussionmentioning
confidence: 71%
“…However, there is accumulating evidence that haploinsufficiency or reduced expression of tumor suppressor genes can influence carcinogenesis (Berger et al 2011). Indeed heterozygosity for Nf1 causes cancer-like cellular phenotypes in astrocytes (Gutmann et al 1999;Bajenaru et al 2001;Gutmann et al 2001). We note that a recent cancer genome study did not report a high frequency of NF1 CNAs (Curtis et al 2012).…”
Section: Discussionmentioning
confidence: 71%
“…In this study, we observed an increased OPN expression in Nf1ϩ/Ϫ osteoblasts and an increased serum level of OPN in Nf1ϩ/Ϫ mice. It has been established that loss of NF1, a GTPase for p21Ras, results in an activation of Ras in a number of lineages (3,10,18,27). The increase in OPN expression in Nf1ϩ/Ϫ mice may be a result of the hyper Ras activity in osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…T-cadherin overexpression was found to be a common feature of human invasive hepatocellular carcinomas (Riou et al, 2006) and high grade astrocytomas, where it was associated with malignant transformation of astrocytes. Hetezygosity for NF1 (neurofibromatosis 1) tumor suppressor resulting in reduced attachment and spreading and increased motility also coincided with upregulated T-cadherin expression (Gutmann et al, 2001).…”
Section: T-cadherin and Tumor Growth And Vascularizationmentioning
confidence: 97%